Innovation platforms and rural advisory services: Feedback from a SEARCA Forum-workshop - International Livestock Research Institute (International Livestock Research Institute, 2016)
Feedback from participants in the SEARCA Forum-workshop on Platforms, Rural Advisory Services, and Knowledge Management: Towards Inclusive and Sustainable Agricultural and Rural Development, Los Banos, 17-19 May 2016.